2022
DOI: 10.3390/ijerph192113731
|View full text |Cite
|
Sign up to set email alerts
|

Using the Oral Assessment Guide to Predict the Onset of Pneumonia in Residents of Long-Term Care and Welfare Facilities: A One-Year Prospective Cohort Study

Abstract: Appropriate oral health care, depending on oral assessments, reduces the onset of pneumonia. However, the relationship between risk evaluation using an oral assessment tool and pneumonia in residents of long-term care facilities has not been fully elucidated. In the present study, we aim to examine the relationship between the total scores of the Oral Assessment Guide (OAG) and the incidence of pneumonia after a one-year baseline study of residents in long-term care facilities. The settings for sampling includ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 41 publications
0
1
0
Order By: Relevance
“…The oral hygiene and the incidence of aspiration pneumonia and nursing and healthcare-associated pneumonia (NHCAP) have been well established. 14 Many studies on geriatric, nursing home, hospitalized, and intensive care unit patients [17][18][19][20][21] have reported an association between oral health and pneumonia. Additionally, Japanese study 22 revealed that infrequent denture cleaning is significantly associated with the incidence of pneumonia.…”
Section: Discussionmentioning
confidence: 99%
“…The oral hygiene and the incidence of aspiration pneumonia and nursing and healthcare-associated pneumonia (NHCAP) have been well established. 14 Many studies on geriatric, nursing home, hospitalized, and intensive care unit patients [17][18][19][20][21] have reported an association between oral health and pneumonia. Additionally, Japanese study 22 revealed that infrequent denture cleaning is significantly associated with the incidence of pneumonia.…”
Section: Discussionmentioning
confidence: 99%